High Frequency Jet Ventilation during Transoral Laser Microsurgery for Tis-T2 Laryngeal Cancer - Mora, Francesco; Missale, Francesco; Incandela, Fabiola; Filauro, Marta; Parrinello, Giampiero; Paderno, Alberto; Della Casa, Palmiro; Piazza, Cesare; Peretti, Giorgio (Frontiers in Oncology, 2017)
Background: Transoral laser microsurgery (TLM) for early to intermediate laryngeal squamous cell cancer (SCC) can be technically challenging when adequate exposure of the posterior laryngeal compartment is required due to the presence of the orotracheal tube. The goal of our study was to analyze the efficacy of high frequency jet ventilation (HFJV) in achieving appropriate laryngeal exposure and safe oncologic resection of lesions located in such a position. Methods: We reviewed the clinical records of 62 patients affected by Tis-T2 SCC of the posterior laryngeal compartment treated by TLM between 02/2012 and 12/2016. The cohort was divided into 2 groups according to the anaesthesiologic technique used: Group A included patients treated using intraoperative infraglottic HFJV, while Group B encompassed patients treated by standard orotracheal intubation. The main outcome was postoperative surgical margin status. Groups comparison analysis was performed. Results: Significant difference in deep margin status was observed between the 2 groups: in Group A, the rate of negative deep margins was 86% compared to 56% in Group B (p=0.04). A trend of better overall and superficial margin control was observed for patients treated using HFJV (Group A), although no statistical significance was achieved. Conclusion: Use of HFJV during TLM allows easier and safer management of patients affected by Tis-T2 SCC of the posterior laryngeal compartment, reducing the rates of positive superficial and deep surgical margins.